Myosin Light Chain Kinase: A Potential Target for Treatment of Inflammatory Diseases - Yongjian Xiong; Chenou Wang; Liqiang Shi; Liang Wang; Zijuan Zhou; Dapeng Chen; Jingyu Wang; Huishu Guo (Frontiers Media S.A., 2017)
Myosin light chain kinase (MLCK) induces contraction of the perijunctional apical actomyosin ring in response to phosphorylation of the myosin light chain. Abnormal expression of MLCK has been observed in respiratory diseases, pancreatitis, cardiovascular diseases, cancer, and inflammatory bowel disease. The signaling pathways involved in MLCK activation and triggering of endothelial barrier dysfunction are discussed in this review. The pharmacological effects of regulating MLCK expression by inhibitors such as ML-9, ML-7, microbial products, naturally occurring products, and microRNAs are also discussed. The influence of MLCK in inflammatory diseases starts with endothelial barrier dysfunction. The effectiveness of anti-MLCK treatment may depend on alleviation of that primary pathological mechanism. This review summarizes evidence for the potential benefits of anti-MLCK agents in the treatment of inflammatory disease and the importance of avoiding treatment-related side effects, as MLCK is widely expressed in many different tissues.